Microfluidic coagulation assay for monitoring anticoagulant therapy in acute stroke patients - Bluecher, Annemarie; dos Santos, Sascha Meyer; Ferreirós, Nerea; Labocha, Sandra; Meyer dos Santos, Isabel Maria Rodrigues; Picard-Willems, Bettina; Harder, Sebastian; Singer, Oliver C. (Thrombosis and Haemostasis, 2017)
Reliable detection of anticoagulation status in patients treated with non-vitamin K antagonist oral anticoagulants (NOACs) is challenging but of importance especially in the emergency setting. This study evaluated the potential of a whole-blood clotting time assay based on Surface Acoustic Waves (SAW-CT) in stroke-patients. The SAW-technology was used for quick and homogenous recalcification of whole blood inducing a surface-activated clotting reaction quantified and visualised by real-time fluorescence microscopy with automatic imaging processing. In 20 stroke or transient ischaemic attack (TIA)-patients taking NOACs kinetics of SAW-CT were assessed and correlated to other coagulation parameters (PT, aPTT) and NOAC-plasma concentration measured by tandem mass spectrometry (LC-MS/MS). In 225 emergency patients with suspicion of acute stroke or TIA, SAW-CT values were assessed. Mean (± SD) SAW-CT in non-anticoagulated stroke patients (n=180) was 124 s (± 21). In patients on dabigatran or rivaroxaban, SAW-CT values were significantly higher 2 and 8 hours (h) after intake rising up to 267 seconds (s) (dabigatran, 2 h after intake) and 250 s (rivaroxaban, 8 h after intake). In patients on apixaban, SAW-CT values were only moderately increased 2 h after intake (SAW-CT 153 s). In emergency patients, SAW-CT values were significantly higher in NOAC and vitamin K antagonist (VKA)-treated as compared to non-anticoagulated patients. In conclusion, the SAW-CT assay is capable to monitor anticoagulant level and effect in patients receiving dabigatran, rivaroxaban and the VKA phenprocoumon. It has a limited sensitivity for apixaban-detection. If specific SAW-CT results were used as cut-offs, SAW-CT yields high diagnostic accuracy to exclude relevant rivaroxaban and dabigatran concentrations in strokepatients.
Keywords: Stroke; acute; factor Xa antagonists/inhibitors; antithrombins; phen-procoumon; whole blood coagulation time